An in-depth exploration of residents' perceived impacts of transient vacation rentals. Issue 1 (2nd January 2018) - Jordan, Evan J.; Moore, Jocelyn
ABSTRACT: The recent explosion of transient vacation rental (TVR) accommodations has been aided by websites like AirBnB, Vacation Rentals By Owner (VRBO), and HomeAway and this segment continues to grow in popularity. Many communities have enacted bans on TVRs with little empirical data to support decisions. This study explores TVR-related impacts as perceived by residents, and why those particular impacts are perceived. A series of 12 semi-structured, in-depth interviews of key resident stakeholders on Oahu, Hawai'i, United States (US) were conducted. Thematic analysis revealed residents perceived both positive and negative impacts in the economic, environmental, and sociocultural realms. Extended quotes from interviewees reveal the connection of perceived impacts to the presence of TVRs in residential zoned areas and the lack of a proprietor to manage the property and tourists like a traditional bed and breakfast (B&B). Findings provide a baseline for future research examining the unique impacts of this area of rapid tourism growth. Marketing implications are discussed.